Maggie moves on eaudiobook - Score, Lucy (2022)
Can these opposites turn up the heat... without burning down the house? House-flipping sensation and YouTube star Maggie Nichols can't wait to dig into her next challenge. Arriving in tiny Kinship, Idaho, with only a cot and a coffeemaker, Maggie is prepared to restore a crumbling Victorian mansion in four months or less. She has her to-do lists, her blueprints, and her team. What she doesn't have is time for sexy, laid-back landscaper Silas Wright. The man takes flirtation to a whole new level. And he does it shirtless...sometimes pants-less. He and his service school-dropout dog are impressively persistent. But she's not interested in putting down roots. Not when fans tune in to watch her travel the country turning dilapidated houses into dream homes. A short-term fling on the other hand could fit nicely into her calendar. After all, Maggie remembers what fun is like. Vaguely. As their summer gets downright steamy, Silas manages to demolish the emotional walls she's spent years building, sending Maggie into a panic. He's the wrench in her carefully constructed plans. With the end of the project looming, she has a decision to make. But how can she stay when her entire career is built on moving on?